2022
DOI: 10.1155/2022/9990854
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Neuropeptide Y within Paraventricular Nucleus in Electroacupuncture Inhibiting Sympathetic Activities in Hypertensive Rats

Abstract: Although electroacupuncture (EA) has been used to decrease the blood pressure (BP) clinically, the underlying mechanisms are not clearly clarified. This study aimed to assess the hypothesis that EA treatment exerts a hypotensive action via suppressing sympathetic activities and modulating neuropeptide Y (NPY) function within the paraventricular nucleus (PVN) of hypertensive rats. Male Sprague-Dawley rats were selected for the experiment, and the hypertensive models were established by the two-kidney, one-clip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Studies have also demonstrated that EA increases the expression of NPY in the hypothalamus and attenuates the stress response under chronic stress conditions [ 20 , 21 ]. Further, EA also induces NPY expression in the paraventricular nucleus and inhibits antihypertensive and sympathetic activities [ 22 ]. EA exerts its protective effect by activating sympathetic alpha-adrenergic receptors in myocardial ischemic injury [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also demonstrated that EA increases the expression of NPY in the hypothalamus and attenuates the stress response under chronic stress conditions [ 20 , 21 ]. Further, EA also induces NPY expression in the paraventricular nucleus and inhibits antihypertensive and sympathetic activities [ 22 ]. EA exerts its protective effect by activating sympathetic alpha-adrenergic receptors in myocardial ischemic injury [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dental ULFTENS, unlike other trigeminal transcutaneous electrical stimulation techniques, is delivered at a frequency of 0.66 hz (Ultra Low), also called Acupuncture-like. Part of its central effects on cardiovascular activity on the PAG-RVLM circuit (Periaqueductal gray-Rostroventrolater medulla circuit) [ 51 , 52 ] and the vagal baroreflex circuit of the nucleus tractus solitarius [ 53 ] could be related to this mode of delivery. On the other hand, collaterals are sent from the PAG-RVLM circuit both to the locus coeruleus and to the caudal part of the nucleus of the solitary tract [ 54 ], largely justifying the functional relationships activated by ULFTENS between PAG-RVLM- Nago-LC nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture can regulate inflammatory diseases, gastrointestinal functional diseases through the ANS as well as cardiovascular, lung, kidney, pancreatic, and other visceral functional diseases. For example, ST36 and ST40 electroacupuncture inhibit sympathetic nerve activity in hypertensive rats, regulate Neuropeptide Y (NPY) expression in the PVN, and reduce blood pressure [65] . Electroacupuncture Jianshi (PC5) and PC6 can inhibit increase in blood pressure by regulating cardiovascular sympathetic neurons in the hypothalamic arcuate nucleus and ventrolateral periaqueductal gray (vlPAG) [66][67] .…”
Section: Application Value Of Autonomic Nerve Regulation Pathway In A...mentioning
confidence: 99%
“…Gastric motility [62] RN12, BL21 Parasympathetic Regulation of gastric motility via the PVN-DVC-vagus-gastric nerve pathway Gastric motility [63] PC6 Parasympathetic Reducing inhibition of efferent vagal motor fibers by inhibiting GABA transmission to the DMV, thereby promoting efferent vagal activity and increasing gastric motility Gastric motility [64] ST36 Parasympathetic The NR2A-containing NMDARs are essential for NMDAR-mediated enhancement of gastric motility caused by stimulating ST36 Hypertension [65] ST36, ST40 Sympathetic Inducing increases in NPY expression and function in the PVN contribute to hypotension and sympathetic inhibition in hypertensive rats Hypertension [66][67] PC5, PC6 Sympathetic/ Parasympathetic Improving autonomic balance, increasing sympathetic and reducing parasympathetic tone; suppresses blood pressure elevation by activating the arcuate nucleus, ventrolateral periaqueductal gray and inhibiting cardiovascular sympathetic neurons in the ventrolateral medulla Acute respiratory distress syndrome [68] ST36…”
Section: Inhibition Of Pro-inflammatory Cytokines Via Autonomic Mecha...mentioning
confidence: 99%